Título Padrão: Pandemic effect on the marine environment: a multisectoral and cross-sectional perception - Soares Melo, Verônica; Torres Pereira, Rafaela; Caetano Zama, Paula (Arquivos de Ciências do Mar, 2022)
The mankind and the sea have a historical relationship of exchanges, which is not always positive for both sides, but which, in a way, has stabilized over time. This scenario commonly under goes local changes, but in the current context of the COVID-19 pandemic, effects on the marine environment can be seen en masse. This work aimed to provide an initial and general overview of the pandemic effects on marine life and coastal environments in Brazil. For this, we conducted a scientific clipping, the collection of testimonies from professionals engaged and active in issues related to the Ocean, and the assessment of litter bulletins on the beaches of the Northeast Coast of São Paulo. The clipping showed positive and negative aspects of the pandemic effect, some of which were discussed in scientific dissemination content that had more than 50 thousand views on the social network Instagram. The testimonies showed the effects caused by the pandemic in the Brazilian territory, providing information not yet published on the benefits and challenges faced in each region. The analysis of the presence of garbage on the beaches, on the other hand, showed the arrival of pandemic garbage in these places, pointing out holidays as peak dates when observing masks on the beaches. Although in several sectors the pandemic has been shown to be both beneficial and harmful to the environment and marine life, the so-called negative effects have had an impact on deeper and more lasting levels. Keywords: environmental impacts, pandemic, sea life, coastal environments, covid-19